(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article is devoted to the study of pejorative words in phraseological units of the Uighur language. From time immemorial, there are norms and rules of behavior in society indicating what is allowed in human behavior and what is prohibited. Of particular interest are the words that contain evaluative-negative, in some way abusive, meaning because they direct a person, teach him to behave properly, to do good deeds. In our view, pejoratives contribute to the formation of the individual’s. These words exist in every language. In this study, the considered pejorative phraseological units of the Uigur language revealed negative features in the behavior, in the human character, and the quantitative analysis helped to make the scale of more or less condemned features in a person. The consideration of pejorative phraseological units allowed to see the connection between the norms of behavior in society and mentality, education, history, lifestyle, national and cultural haracteristics of the Uigur people, understand the nature of pejorative words in phraseologisms of the Uigur language.